Anatomo-pathological lesions in guinea pigs experimentally intoixcated with pteridium aquilinum as a model animal for cattle with bovine enzootic haematuria - Ramos G., Mariella (2012)
The study describes the development of pathological lesions in guinea pigs (Cavia porcellus) experimentally intoxicated through the ingestion of pellets containing one third of Pteridium aquilinum and two thirds of concentrate during 135 days. The guinea pig was used as a experimental model for cattle with Bovine Enzootic Haematuria (BEH). Twelve female animals with a mean of 400 g body weight were used. Two of them, selected at random, were slaughtered on days 30, 60, 90 and 120 days and the last 4 on day 135 of the trial. The lesions developed were neoplastic, inflammatory, degenerative and adaptation processes. Tumors mainly developed in the bladder, lung, intestine, spleen and lymph nodes. In the bladder, epithelial neoplasms (transitional cell carcinomas) and nonepithelial neoplasms (leiomyosarcoma and myxoma), together with inflammatory processes (chronic nonsuppurative cystitis) and vascular processes (telangiectasia and edema suburotelial) developed. In the lung, intestine, spleen and lymph nodes, most tumors were malignant lymphoma with inflammatory processes such as bronchopneumonia, enteritis and splenitis. Among the proliferative processes, racemose intestinal epithelial hyperplasia and lymphoid follicular hyperplasia in the intestine, spleen and lymph nodes were observed. Most of the processes including neoplasms were noted as of 30 days. It is concluded that guinea pig can be used as experimental animal model for bovine BEH as develops inflammatory lesions, degenerative, adaptation processes and similar neoplasms in the urinary bladder.